2016
DOI: 10.5055/jem.2015.0213
|View full text |Cite
|
Sign up to set email alerts
|

Emergency preparedness of families of children with developmental disabilities: What public health and safety emergency planners need to know

Abstract: Objective To assess the emergency preparedness knowledge, behaviors, and training needs of families of children with developmental disabilities (DD). Design An online survey. Participants A sample of 314 self-selecting US parents/guardians of children with DD, aged birth-21 years. Main outcome measures 1) Preparedness self-assessment; 2) self-report regarding the extent to which families followed 11 specific preparedness action steps derived from publicly available preparedness guides; and 3) parent trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…Parents were surveyed regarding the following: making plans, stockpiling and/or gathering information, holding a family emergency preparedness discussion, developing and practicing a written emergency plan, developing an emergency medical information sheet, knowledge of a public emergency shelter location and accessibility, familiarity and previous interaction with local emergency resources, and disaster planning with schools. They reported that while most participants reported “somewhat” to “moderate” levels of being well prepared, they had taken fewer than half of the recommended 11 action steps and expressed a need for training in preparedness support [ 36 ••].…”
Section: Natural Disasters and Terrorismmentioning
confidence: 99%
“…Parents were surveyed regarding the following: making plans, stockpiling and/or gathering information, holding a family emergency preparedness discussion, developing and practicing a written emergency plan, developing an emergency medical information sheet, knowledge of a public emergency shelter location and accessibility, familiarity and previous interaction with local emergency resources, and disaster planning with schools. They reported that while most participants reported “somewhat” to “moderate” levels of being well prepared, they had taken fewer than half of the recommended 11 action steps and expressed a need for training in preparedness support [ 36 ••].…”
Section: Natural Disasters and Terrorismmentioning
confidence: 99%
“…Children who require special health care are particularly vulnerable to disasters, and preparedness based on their inherent health issues and special training for emergencies is needed [ 39 , 40 ]. Coordination with local service providers can increase preparedness and training for managing emergencies [ 41 ]. It is therefore important for nurses and public health nurses in charge of support to work with children and families who would need to evacuate.…”
Section: Discussionmentioning
confidence: 99%
“…According to Adiwijaya (2017), disaster knowledge is the ability to remember events or series of events that threaten or disrupt people's lives and livelihoods caused by natural or non-natural factors or human factors. From the results of other studies, it is also stated that families with children with disabilities need to anticipate and plan for handling in the face of disasters (Wolf-fordham et al, 2017).…”
Section: Knowledge Of Disasters In Families With Children With Disabilitiesmentioning
confidence: 99%